Gene expression and protein localization of TLR-1, -2, -4 and -6 in amniochorion membranes of pregnancies complicated by histologic chorioamnionitis - Moço, Natália P.; Martin, Laura F.; Pereira, Ana Carolina; Polettini, Jossimara; Peraçoli, José Carlos [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP]; Silva, Marcia Guimarães da [UNESP] (Elsevier, 2013)
Objectives: To determine whether histologic chorioamnionitis is associated with changes in gene expression of TLR-1, -2, -4 and -6, and to describe the localization of these receptors in fetal membranes. Study design: A total of 135 amniochorion membranes with or without histologic chorioamnionitis from preterm or term deliveries were included. Fragments of membranes were submitted to total RNA extraction. RNA was reverse transcribed and the quantification of TLRs expression measured by real time PCR. Results: All amniochorion membranes expressed TLR-1 and TLR-4, whereas 99.1% of membranes expressed TLR-2 and 77.4% expressed TLR-6. TLR-1 and TLR-2 expressions were significantly higher in membranes with histologic chorioamnionitis as compared to membranes without chorioamnionitis in preterm pregnancies (p = 0.003 and p < 0.001, respectively). Among the membranes of term pregnancies there were no differences in the expressions of such receptors regardless of inflammatory status. Regarding TLR-4 and TLR-6 expression, there was no difference among membranes with or without histologic chorioamnionitis, regardless gestational age at delivery. TLR-1, TLR-2, TLR-4 and TLR-6 expressions were observed in amniotic epithelial, chorionic and decidual cells. Conclusion: Amniochorion membranes express TLR-1, TLR-2, TLR-4 and TLR-6 and increased expression of TLR-1 and TLR-2 is related to the presence of histologic chorioamnionitis in preterm pregnancies. This study provides further evidence that amniochorion membranes act as a mechanical barrier to microorganisms and as components of the innate immune system. © 2013 Elsevier B.V. All rights reserved.
Keywords: Amniochorion membranes; Histologic chorioamnionitis; Preterm delivery; Real time PCR; Toll-like receptors